Le lit provenant du château d’Effiat (Puy-de-Dôme) conservé au musée du Louvre - Agnès Bos (In Situ)
The bed which originally came from the Effiat chateau in the Puy-de-Dôme department and which is presented today in the Louvre, in the rooms of the department devoted to art objects, is well known as one of the rare surviving examples of a ‘French-style’ bed of the seventeenth century. It is remarkable for the richness of the textiles it comprises, made up of strips of embossed silk velvet, alternating with strips decorated with embroidery applications. The bed was acquired by the Cluny museum in 1856 when a part of the furniture of the Effiat chateau was auctioned off. It was transferred to the Louvre after the Second World War. It was always thought to be the bed of the Marshall d’Effiat (1581-1632), an influential minister of Louis XIII, closely associated with the Cardinal de Richelieu, whose family chateau he had helped rebuild. However, none of the beds described in his inventory after death seem to correspond with the bed at the Louvre today, whilst it is possible to see correspondences with the description of a bed belonging to Martin Ruzé d’Effiat (1612-1644), the Marshall’s son. The hypothesis today is that the bed was made for this son. When it entered the public museum collections, the bed was in a sorry state of conservation and its textile trimmings were particularly fragile. During the 1960s, a major restoration campaign was undertaken by the Brocard firm on the bed and on some armchairs, but a close examination of the bed shows that it had already seen earlier changes, notably to its wooden structure.